Natural Environment in Ali Muhammad Farshi’s Poems: In context of Eco Criticism - Ikram, Muhammad; Mahmood Asif (Arshad Meraj), Arshad (sourcecoder, 2022)
Ali Muhammad Farshi is a famous poet. His poems are multidimensional. One of main topic of his poems is natural environment. He beautifully present the case of nature survival in his poems. In context of eco criticism (a literary theory that is the study of the relationship between literature and the physical environment) his poems have been analyzed in this article.